Meningkatkan Motivasi dan Prestasi Belajar Bahasa Indonesia dengan Menggunakan Model Pembelajaran CIRC dan Media Pembelajaran Quizizz - Lestari, Winda; Ernawati, Asih (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
: This study aims to improve students' motivation and learning achievement by using the Cooperative Integrated Reading and Composition (CIRC) learning model and learning media. This research is a class action research (PTK) with the research subjects of all fourth grade students of SD Negeri 2 Banjarsari Wetan. The research procedure was carried out in three cycles, consisting of 4 stages, namely 1) planning, 2) implementation, 3) observation and 4) reflection. Data collection was done through initial interviews and non-participant observation, questionnaires and tests. The results showed an increase in student motivation and learning achievement from cycle I to cycle III. Student learning motivation has increased, in cycle I obtained 56.16%, cycle II obtained 64.27%, and cycle III obtained 74.16%. Student learning achievement increased from cycle I obtained 38.83%, cycle II obtained 61.1%, and cycle III obtained 77.77%. It can be concluded that the Cooperative Integrated Reading and Composition (CIRC) learning model by utilizing quizizz learning media can increase the motivation and learning achievement of fourth grade students of SD Negeri 2 Banjarsari Wetan.